The concept of decision support system in preliminary investigation - Sergey V. Duga; Aleksey G. Sebyakin; Andrey I. Trufanov; Lyudmila L. Nosyreva (Безопасность информационных технологий, 2019)
Based on the developed network ontology of the subject area "Preliminary investigation" a conceptual model of the information and analytical decision support system is proposed as a response to the challenge of the increasing need for the analysis of "big data" in the course of a crime investigation. It is demonstrated the importance of automated collection and processing of a variety of information obtained during the individual investigations based on the analysis of network interaction of persons involved in 12 criminal cases.